The Impact of Parents Attitudes on Their Children’s Distance Learning during COVID-19 Outbreak - Harisa Mardiana (Universitas Sebelas Maret, 2021)
Due to the COVID-19 outbreak that spread throughout the world, many activities were carried out at home, especially learning conducted online. The purpose of this study was to describe the impact of parents' attitudes on children in online learning. This study used a qualitative method by conducting interviews with four seventh grades parents, three of seventh grades teachers as representatives of the school, and three of seventh grades students. The results obtained are that parents need guidance in teaching children, extraordinary patience. On the other sides, teachers as facilitators can provide collaborate with parents to educate students. In contrast, students can convey their opinions to teachers about how to learn with parents, and teachers can help parents and students in online learning. Hence, learning for the COVID-19 outbreak can run smoothly so that student education will not be left behind due to the COVID-19 outbreak